Organizational Communication Practices and Work Performance of Healthcare Workers in Antipolo City Hospital System - Ramos, Maria Rosario (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the organizational communication practices and work performance of healthcare workers in the Antipolo City Hospital System during Calendar Year 2025. Specifically, it assessed the respondents’ profile, the extent of organizational communication practices in terms of verbal, non-verbal, written, and visual communication, the challenges encountered in workplace communication, the level of work performance based on Individual Performance Commitment and Review (IPCR) ratings, and the significant differences and relationships among the variables. The study employed a descriptive-correlational survey research design complemented by documentary analysis. A researcher-made questionnaire served as the primary instrument for gathering data, while documentary analysis was used to obtain the respondents’ latest IPCR ratings. The respondents consisted of the total population of 108 healthcare workers from Antipolo City Hospital System Annex II, Annex III, and Annex IV, including doctors, nurses, midwives, pharmacists, medical technologists, and other hospital personnel. Findings revealed that the respondents were predominantly female, single, aged 31 years and above, bachelor’s degree holders, and had more than five years of service, with most attending hospital- and provincial-level seminars and training programs. Verbal communication was consistently practiced, while non-verbal and written communication were often practiced, and visual communication was sometimes utilized. Significant differences in organizational communication practices were found when respondents were grouped according to age, educational attainment, position title, length of service, and seminars or trainings attended, whereas no significant differences were observed based on sex and civil status. Healthcare workers obtained a Very Satisfactory level of work performance based on their IPCR ratings. Furthermore, organizational communication practices were significantly related to work performance. The study concluded that effective organizational communication contributes to improved employee performance and that professional development opportunities enhance communication competencies. It is recommended that hospitals strengthen communication systems, expand training opportunities, allocate adequate resources to improve healthcare services, address communication challenges, and implement the proposed action plan. Future studies may explore additional variables affecting organizational communication and employee performance..